The Marriage Ceremony of Ngajet Penjor in Mass Marriage System in the Pengotan Traditional Village, Bangli - Lali Yogantara, I Wayan (Jurnal Penelitian Agama Hindu, 2023)
Mass weddings in Pengotan Bangli Traditional Village are usually held twice a year, on sasih Kapat and Kadasa. Among the systems of mass marriages is Ngajet Penjor marriage which is held after every pujawali at the Puseh-Bale Agung Temple. The research was conducted with the aim of analyzing the function and meaning of Ngajet Penjor wedding ceremony in mass marriage system in the Pengotan Traditional Village. Data were collected by interview and document study. Data analysis was carried out through the following steps data reduction, display data, conclusions; and verification. The Ngajet Penjor wedding ceremony is held on sasih Kadasa after pujawali at the Puseh-Bale Agung, after penjor ceremony is removed which is used during pujawali. This wedding ceremony took place at Bale Agung Temple which was attended by a number of pairs of bride and groom. The Ngajet Penjor wedding ceremony in mass marriage system functions as a purification and validation of status, as a request to be able to think positively, creatively, innovatively and productively; it also functions socially, fosters cooperation and promotes unity; cost efficiency, and preservation of ancestral culture. The Ngajet Penjor wedding ceremony has a constructive meaning, namely the meeting between Purusa (groom) and Pradana (bride) in a family relationship (husband and wife); evaluative meaning, namely the willingness to establish a legal husband-wife sacred relationship; cognitive meaning, namely fostering social and cultural harmonization, kinship relations due to marriage in accordance with traditional provisions; expressive meaning, namely marriage to create a happy family physically and mentally.